Hambatan-Hambatan Dalam Pengembangan Objek Wisata Air Terjun Pelangai Gadang, Kenagarian Pelangai Gadang Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan - Vina Afrilia; M. Julis; Riri Lestari (Indonesian Journal of Glasial Geography, 2024)
This study discusses the Obstacles in the Development of Tourism Objects Pelangai Pelangai Gadang Waterfall, Ranah Pesisir Selatan District, Pesisir Selatan Regency. The purpose of this study is to describe the Obstacles in the Development of Pelangai Gadang Waterfall Tourism Object, Ranah Pesisir Subdistrict, South Pesisir Regency based on three components, namely Attractions, Accessibility and Amenity. This type of research is a descriptive study using qualitative methods. The sample of this research is the Tourism Object Manager, the community around the attraction of 2 people, and visitors amounting to 5 people in the tourist attraction. There are two data collected, namely Primary Data and Secondary Data. Primary data were obtained from interviews with the research sample, while secondary data were obtained from the Wali Nagari Pelangai Gadang Office, Ranah Pesisir Sub-District Office, Nagari Pelagai Gadang Community Leader. The research findings are obtained; 1) the total score of the Pelangai Waterfall tourist attraction is 38% and included in the weak category 2). The total score of Tourism Accessibility of Gadang Pelanggai Waterfall is 27% included in the weak category 3). Amenitas, the number of safety scores in the Waterfall Objects of Pelangai Gadang 28% is a weak category. So, it can be concluded that in general Tourist Attractions, Accessibility and Amity of the attractions of the Gadang Pelangi Waterfall is in the weak category so that it becomes a major obstacle in the Development of the Pelangai Gadang Waterfall Tourism Object.